Indeterminacy and multiplicity of equilibria in a two-sector economy with a public-sector production - Aleksandar Vasilev (Journal of Economics and Econometrics, 2019)
We introduce government production of both output-augmenting and utility-enhancing public services into an exogenous growth model with a detailed government sector, and calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We show that in contrast to the case without government output, e.g., Vasilev (2009), when the economy features saddle-path stability, the presence of a second sector leads to equilibrium indeterminacy in the model. When public sector production adds to private sector output, the setup exhibits "sink" dynamics, and equilibrium paths are determined by "animal spirits." These results are in line with the findings in the literature, e.g., Benhabib and Farmer (1994, 1996) and Farmer (1999), and have major implications for policy-making and welfare.
Keywords: E32; E22; 330; Equilibrium indeterminacy; government production; animal spirits; two-sector model